PELESTARIAN IDENTITAS LOKAL MELALUI EDUKASI BUDAYA RUMAH LIMAS PADA GENERASI MUDA - Dita Mayreista; Diany Putri Pratiwi Saladin; Abdurrahman Arif; Budi Santoso (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Rumah Limas is a traditional house of South Sumatra that contains cultural, social, and philosophical values as a local identity of the Palembang community. However, modernization and globalization have led to a decline in public understanding, especially among the younger generation, regarding local culture, including Rumah Limas. This community service activity aims to improve cultural literacy regarding Rumah Limas as the local identity of South Sumatra through a cultural communication approach. The method used was a qualitative approach with descriptive field methods and communal action. The activity was conducted at Museum Balaputera Dewa involving junior and senior high school students, youth communities, local communities, visitors, cultural experts, and Rumah Limas owners. Data collection techniques included observation, interviews, discussions, and documentation. The results showed an increase in participants’ understanding of the history, philosophy, social functions, and cultural values of Rumah Limas after participating in cultural education activities. Participants also demonstrated greater enthusiasm and awareness regarding the importance of preserving local culture as the identity of the South Sumatran community. This activity indicates that a cultural communication approach can be an effective medium for improving community cultural literacy and supporting the preservation of regional cultural heritage.